BRASSINOSTEROID-SIGNALING KINASE1 modulates MAP KINASE15 phosphorylation to confer powdery mildew resistance in Arabidopsis. Issue 5 (31st January 2022) - Shi, Hua; Li, Qiuyi; Luo, Mingyu; Yan, Haojie; Xie, Bao; Li, Xiang; Zhong, Guitao; Chen, Desheng; Tang, Dingzhong
Abstract: Perception of pathogen-associated molecular patterns (PAMPs) by plant cell surface-localized pattern-recognition receptors (PRRs) triggers the first line of plant innate immunity. In Arabidopsis thaliana, the receptor-like cytoplasmic kinase BRASSINOSTEROID-SIGNALING KINASE1 (BSK1) physically associates with PRR FLAGELLIN SENSING2 and plays an important role in defense against multiple pathogens. However, how BSK1 transduces signals to activate downstream immune responses remains elusive. Previously, through whole-genome phosphorylation analysis using mass spectrometry, we showed that phosphorylation of the mitogen-activated protein kinase (MAPK) MPK15 was affected in the bsk1 mutant compared with the wild-type plants. Here, we demonstrated that MPK15 is important for powdery mildew fungal resistance. PAMPs and fungal pathogens significantly induced the phosphorylation of MPK15 Ser-511, a key phosphorylation site critical for the functions of MPK15 in powdery mildew resistance. BSK1 physically associates with MPK15 and is required for basal and pathogen-induced MPK15 Ser-511 phosphorylation, which contributes to BSK1-mediated fungal resistance. Taken together, our data identified MPK15 as a player in plant defense against powdery mildew fungi and showed that BSK1 promotes fungal resistance in part by enhancing MPK15 Ser-511 phosphorylation. These results uncovered a mechanism of BSK1-mediated disease resistance and provided new insight into the role of MAPK phosphorylation in plant immunity. Abstract : Arabidopsis BSK1 physically associates with MPK15 and is required for pattern- and pathogen-induced MPK15 Ser-511 phosphorylation, which contributes to BSK1-mediated powdery mildew resistance.